JUDICIAL ETHICS AND THE INFLUENCE OF MORAL MOTIVES ON JUDICIAL DECISION-MAKING - Tilovov, Murodulla (International Conference on Science, Education & Law, 2025)
This article explores the philosophical and ethical foundations of judicial ethics and the role of moral motives in judicial decision-making. The study examines how moral reflection, conscience, and civic responsibility influence the fairness and legitimacy of judicial decisions. The research also analyzes the views of scholars such as Israilova, Abdurakhmanova, Talapov, Babajonov, Luban, Radbruch, Ricoeur, and Rodotà to demonstrate that judicial ethics represent not only professional conduct but also a manifestation of moral reasoning within the legal order. The article concludes that the legitimacy of the judiciary depends on its ability to harmonize legal norms with moral imperatives, thus ensuring justice, human dignity, and social trust.